2002
DOI: 10.1080/07315724.2002.10719248
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids in Inflammation and Autoimmune Diseases

Abstract: Among the fatty acids, it is the omega-3 polyunsaturated fatty acids (PUFA) which possess the most potent immunomodulatory activities, and among the omega-3 PUFA, those from fish oil-eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)--are more biologically potent than alpha-linolenic acid (ALA). Some of the effects of omega-3 PUFA are brought about by modulation of the amount and types of eicosanoids made, and other effects are elicited by eicosanoid-independent mechanisms, including actions upon intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
932
5
62

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,635 publications
(1,072 citation statements)
references
References 83 publications
27
932
5
62
Order By: Relevance
“…It was previously reported that using supplemental fat might improve the energy balance and increase birth weight in shame goats (Titi and Awad, 2007;Eghoghosoa et al, 2011). Fatty acid supplements may also improve the ability to use nutrients from the food and convert them into muscle protein (Simopoulos, 2002). A study conducted by Okukpe et al (2011) confirmed the present finding, in which they observed an improvement of weight gain in goats fed omega-3 fatty acid as a supplement, but this correlation did not achieve significance.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that using supplemental fat might improve the energy balance and increase birth weight in shame goats (Titi and Awad, 2007;Eghoghosoa et al, 2011). Fatty acid supplements may also improve the ability to use nutrients from the food and convert them into muscle protein (Simopoulos, 2002). A study conducted by Okukpe et al (2011) confirmed the present finding, in which they observed an improvement of weight gain in goats fed omega-3 fatty acid as a supplement, but this correlation did not achieve significance.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, five fatty acids were considered of interest, i.e. arachidonic acid (AA, 20:4n-6), EPA, and DHA, which are implicated in physical and mental health [19][20][21], the DHA status parameter adrenic acid (AdrA, 22:4n-6), and docosapentaenoic acid (DPA, 22:5n-3), which is a major intermediate in EPA-to-DHA conversion.…”
Section: Fatty Acid Statusmentioning
confidence: 99%
“…N-3 PUFAs may suppress proinflammatory TNF-a and IL-1 production and actions, while n-6 PUFAs have the opposite effect. Indeed, patients with autoimmune diseases, such as rheumatoid arthritis, inflammatory bowel disease and asthma, responded well to supplementation with long-chain n-3 fatty acids EPA and DHA by decreasing disease-associated elevated levels of cytokines (Simopoulos, 2002). In addition, fish oil supplementation of newly diagnosed MS patients increased the plasma phospholipid n-3 fatty acids and decreased the n-6 fatty acids, resulting in significant reduction of exacerbations and the EDSS clinical score (Nordvik et al, 2000).…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%